Multi-keyword attribute-based searchable encryption scheme supporting re-encryption for cloud storage - ZHANG Kejun; WANG Wenbin; XU Shaofei; YU Xinying; WANG Jun; LI Pengcheng; QIAN Rong (Tongxin xuebao)
To address fine-grained access control, secure sharing, and encrypted key updates in a one-to-many model, a multi-keyword attribute-based searchable encryption scheme with proxy re-encryption for cloud storage was proposed. The access tree was enhanced with node information for fine-grained control over ciphertext read and write permissions. The keyword encryption process was optimized for trapdoor indistinguishability and restricted user search capabilities. Re-encryption updated ciphertext and keys, preventing malicious access by revoked users. A blockchain-based verification algorithm was designed to detect tampering of third-party data. The DBDH and DDH hard problems proved the scheme’s keyword ciphertext security and trapdoor security. Experiments show the proposed scheme secures data and keys during key generation, trapdoor, and index generation, and correctness verification. It also demonstrates higher efficiency in time overhead, ensuring privacy and key safety while maintaining high efficiency.